2011
DOI: 10.1002/jmri.22668
|View full text |Cite
|
Sign up to set email alerts
|

Strenuous resistance exercise effects on magnetic resonance diffusion parameters and muscle–tendon function in human skeletal muscle

Abstract: Purpose: To assess the effects of strenuous exercise on magnetic resonance diffusion parameters and muscletendon complex function in skeletal muscle. Materials and Methods:Six men performed ankle plantar flexion exercises with eccentric contraction. The fractional anisotropy (FA), l 1 , l 2 , l 3 , mean diffusivity (MD), and T 2 values in the triceps surae muscles were measured by magnetic resonance diffusion tensor and spinecho imaging. Passive torque of plantar flexors, maximal voluntary isometric plantar fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…Previous research established DTI as a reproducible and valid technique (23,24,26) to evaluate muscle status (10,11,(27)(28)(29). We extended the clinical applicability of this technique by developing a protocol that covers both upper legs from hip to knee in one examination.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research established DTI as a reproducible and valid technique (23,24,26) to evaluate muscle status (10,11,(27)(28)(29). We extended the clinical applicability of this technique by developing a protocol that covers both upper legs from hip to knee in one examination.…”
Section: Resultsmentioning
confidence: 97%
“…The DTI-derived parameters-eigenvalues (l 1 , l 2 , and l 3 ), mean diffusivity, and fractional anisotropy (FA)-are sensitive to changes in the tissue microstructure. Previous studies showed increase of mean diffusivity and decrease of FA within skeletal muscle tissue after mechanical injury and exercise-induced trauma (10)(11)(12). However, these studies measured the diffusion in small parts of muscles with known abnormalities.…”
mentioning
confidence: 96%
“…To support the usefulness of T 2 as an index of muscle damage, high correlation ( r  > 0.9) has been reported between changes in T 2 and plasma CK activity measured within several days after eccentric exercises 30, 38 . Some studies demonstrated that T 2 increased heterogeneously within the KEs 11, 31, 37 or PFs 39, 40 after eccentric or strenuous resistance exercises. To the authors knowledge, however, no studies have examined localization of muscle damage within the KEs and PFs induced by DR. Clarifying this would provide insight into which site or muscle should be given particular care and/or focus when conducting DR in a practical or experimental setting.…”
Section: Introductionmentioning
confidence: 99%
“…FA will show the degree of water diffusion anisotropy according to the muscle fiber direction. Thus, the FA value is a robust intravoxel measure that yields values between 0 (perfectly isotropic) and 1 (perfectly anisotropic) (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, combining these per-voxel data sets will permit the construction of 3-dimensional fiber tracts Furthermore, the parameters FA and ADC can be evaluated from these data sets, supplying a quantitative description of tissue organization and integrity (13,14,24). DTI is based on the fact that cell membranes and other structures restrict water diffusion through the tissues, leading to anisotropic diffusion (19). DTI anatomically represents the diffusion along the main direction of the muscle fiber (20).…”
Section: Discussionmentioning
confidence: 99%